THE RELATIONSHIP BETWEEN COMPETENCY AND SERVICE OFFICERS ON THE ACHIEVEMENT OF EXCLUSIVE BREASTFEEDING TARGETS IN KENDARI CITY HEALTH DEPARTMENT: EXCLUSIVE BREASTFEEDING TARGETS - Asmawati Asmawati; Tasnim Tasnim; Sunarsih Sunarsih (STIKes Mandala Waluya Kendari, 2021)
Background:The coverage of exclusive breastfeeding in Kendari City is in the 4th (fourth) lowest place out of 17 city districts in Southeast Sulawesi Province. Although Kendari City is not in the lowest rank, it will be used as a research area considering that the number of children under five in Kendari City is the highest in Southeast Sulawesi Province, so it is necessary to get attention to carry out programs to increase the coverage of exclusive breastfeeding. Methods:The type of research used in this study isquantitative with an observational method with a cross sectional approach.The population was 150 with 59 samples of all health workers (KIA, Gizi and Promkes) in the Kendari City Health Office Work Area. Results:The results of statistical tests using Chi-Square obtained the value of X2 hit> X2 tab 4,262> 3,841 with Sig. 0.039 <? 0.05 and a phi value of 0.290, namely Ha accepted, which means that there is a weak relationship between the competence of officers and the target achievement of exclusive breastfeeding and the value of X2 hit> X2 tab 7,884> 3,841 with Sig. 0.005 <? 0.05 with a phi value of 0.371, which is Ha accepted, which means that there is a moderate relationship between health care services and the achievement of the target of exclusive breastfeeding in the work area of ??the Kendari City Health Office. Conclusion:There is a weak relationship between the competence of health workers and the achievement of targets for exclusive breastfeeding and there is a moderate relationship between health services and the achievement of targets for exclusive breastfeeding in the working area of ??the Kendari City Health Office.